Efficacy of ceftaroline against methicillin-susceptible Staphylococcus aureus exhibiting the cefazolin high-inoculum effect in a rat model of endocarditis - Singh, Kavindra V. (2017)
Certain Staphylococcus aureus strains exhibit an inoculum effect (InE) with cefazolin (CFZ) that has been associated with therapeutic failures in highinoculum infections. We assessed the in vitro activities of ceftaroline (CPT), CFZ, and nafcillin (NAF) against 17 type A β-lactamase (βla)-producing, methicillin-susceptible S. aureus (MSSA) strains, including the previously reported TX0117, which exhibits the CFZ InE, and its βla-cured derivative, TX0117c. Additionally, we determined the pharmacokinetics of CPT in rats after single intramuscular doses of 20 and 40 mg/kg of body weight and evaluated the activities of CPT (40 mg/kg every 8 h [q8h]), CFZ, and NAF against TX0117 and TX0117c in a rat model of infective endocarditis. No InE was observed for CPT or NAF, whereas a marked InE was detected for CFZ (MIC, 8 to ≥128 μg/ml). CPT and NAF treatment against TX0117 resulted in mean bacterial counts of 2.3 and 2.1 log10 CFU/g in vegetations, respectively, compared to a mean of 5.9 log10 CFU/g in the CFZ-treated group (CPT and NAF versus CFZ, P = 0.001; CPT versus NAF, P = 0.9830). Both CFZ and CPT were efficacious against the βla-cured derivative, TX0117c, compared to time zero (t0) (P = <0.0001 and 0.0015, respectively). Our data reiterate the in vivo consequences of the CFZ InE and show that CPT is not affected by this phenomenon. CPT might be considered for highinoculum infections caused by MSSA exhibiting the CFZ InE.